Importance of Dental Aesthetics Among Young Adults - A Survey - NIVEDHITA, G.; KOMMI, VENKATESH; SASHANK, KEERTHI; BRUNDHA, M.P. (The journal of contemporary issues in business and government, 2020)
Smiling is one of the important factors of life that creates an impression on a person. Being dentally aesthetic and physically well presentable boosts your confidence on a higher level. Yet this might be affected by certain habits during the growth of permanent teeth. Prevalence of malocclusion and misalignment is higher in adolescent children, thereby the confidence might get hit. The aim of this study is to see how much importance is given to dental aesthetics by young adults. The study subjects were 165 young adults aged 12-20 years, where they answered a questionnaire of 11 questions dealing with dental aesthetics and its psychological impact. Statistical analysis (Chi-square) was run on the data collected using SPSS software version 23. The results showed that even in such a competitive world to stand out from the crowd most people still chose to flaunt their flaws and lead a happy life and be successful. The results of the survey showed that there is no significant relationship between misalignment and mental wellness on the respondents. It also showed that the respondents did not find any impact in their professional or personal success due to the incidence of misalignment. The future scope of this study is that it would create awareness among people on the effect of dental aesthetics on a person and change the behavior/ way of treating people.